PENGARUH KUALITAS PELAYANAN LABORAN LABORATORIUMIPA TERHADAP TINGKAT KEPUASANSISWA : Studi Kasus SMA NEGERI 5 PURWOREJO (Prospect : Jurnal Manajemen dan Akuntansi, 2018)
This study aims to determine whether there is a positive and significant influence between the quality of service to the level of student satisfaction. In this study the quality of service includes reliability, responsiveness, assurance, empathy and physical evidence. Data collection techniques used are obervation techniques, interview techniques, questionnaires and documentation techniques. The population numbered 288 students and the number of seals 29 students or10% of the total population. The sampling technique used stratified random sampling, the data were analyzed by, simple linear regression, coefficient of determination and t test. Regression analysis results obtained a = 4.719 and b = 0.797 then the regress ion equation formed is Y = 4.719 + 0.797 X. The value of determination coefficient of 0.257 means that the influence of service quality to student satisfaction level is 25.7% and the remaining 74.3% affected Other factors beyond service quality include hardware, software, hardware quality, value-added software quality and learning process. Hypothesis testing can be proved there is apositive and significant influence between the quality of laboratory laboratory service laboratory to the satisfaction of students of SMA Negeri 5 Purworejo, so Ho is rejected and Ha accepted.